2020
DOI: 10.1039/d0qm00075b
|View full text |Cite
|
Sign up to set email alerts
|

Multiring-induced multicolour emission: hyperbranched polysiloxane with silicon bridge for data encryption

Abstract: The presented work shows an impressive multicolour luminescence hyperbranched polysiloxane attributed to the multiring through-space conjugation named “multiring induced multicolor emission” (MIE), as well as its application in data encryption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 39 publications
1
83
0
Order By: Relevance
“…Furthermore, recently, our group found that a novel hyperbranched polysiloxane exhibited similar phenomenon, that is, different‐sized electron delocalization emitted different color light. [ 28 ] However, in Figure 4C, the electron delocalization of P0 is homogeneous; thus, the band gaps of HOMO‐LUMO orbits of most electron delocalization are similar, which is the reason only blue light is generated. It is obvious that P0, P1, and P2 have different molecular structures.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recently, our group found that a novel hyperbranched polysiloxane exhibited similar phenomenon, that is, different‐sized electron delocalization emitted different color light. [ 28 ] However, in Figure 4C, the electron delocalization of P0 is homogeneous; thus, the band gaps of HOMO‐LUMO orbits of most electron delocalization are similar, which is the reason only blue light is generated. It is obvious that P0, P1, and P2 have different molecular structures.…”
Section: Resultsmentioning
confidence: 99%
“…This insensitivity of emission versus the tested solvents suggests the negligible solvent effect on the cluster structure, i.e. weak interaction between solvent and TPU chains, which is different from hyperbranched polysiloxane, where obvious changes of the emission intensity was observed in different solvents [65].…”
Section: Tests Of Cluster Formationmentioning
confidence: 91%
“…The quenching effect of Fe 3+ has been often studied for different fluorescent materials [65][66][67][68][69]. Different mechanisms have been proposed for the selectivity of Fe 3+ .…”
Section: Quenching Effect and Application Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with conventional aggregation-induced emission (AIE) luminogens, 1,2 non-aromatic AIE polymers 3,4 is emerging in biological imaging, metal ion detection and other fileds 1,4,5 due to their low toxicity and excellent environmental friendliness. However, the species of non-aromatic AIE polymers are mainly limited to the N-containing polymers such as poly(amino ester)s, [6][7][8] poly(amidoamine)s, 9 polyethylenimines, 10 etc.…”
Section: Introductionmentioning
confidence: 99%